Enhanced electrochemical performance of lithium ion batteries using Sb2S3 nanorods wrapped in graphene nanosheets as anode materials - Dong, Yucheng (2020)
Antimony sulfide can be used as a promising anode material for lithium ion batteries due to its high theoretical specific capacity derived from sequential conversion and alloying lithium insertion reactions. However, the volume variation during the lithiation/delithiation process leads to capacity fading and cyclic instability. We report a facile, one-pot hydrothermal strategy to prepare Sb2S3 nanorods wrapped in graphene sheets that are promising anode materials for lithium ion batteries. The graphene sheets serve a dual function: as heterogeneous nucleation centers in the formation process of Sb2S3 nanorods, and as a structural buffer to accommodate the volume variation during the cycling process. The resulting composites exhibit excellent electrochemical performance with a highly reversible specific capacity of ∼910 mA h g−1, cycling at 100 mA g−1, as well as good rate capability and cyclic stability derived from their unique structural features.